Dziadkowie spadkodawcy i ich zstępni jako spadkobiercy ustawowi – uwagi de lege lata i de lege ferenda w świetle projektu nowelizacji Kodeksu cywilnego - Anna Paluch (Acta Iuris Stetinensis, 2024)
The purpose of the article is to answer the question, whether Article 934 of the Polish Civil Code outlines the subjective boundaries of statutory inheritance correctly and adequately to contemporary social realities, and whether there are reasons for limiting the degree of kinship between the deceased’s ascendants or their descendants and the deceased. The draft amendment of the Civil Code and certain other acts (Parliamentary Document no. 2977) became an impulse to take up this discussion. The draft is analysed within the scope of the proposed amendment to Article 934 of the Polish Civil Code. The analysis leads to the conclusion that the statutory inheritance of grandparents has been rightly introduced into the civil code, while the current wording of Article 934(2) of the Civil Code outlines the circle of persons called to statutory inheritance too broadly, without providing for any limitation of grandparents’ descendants in terms of the degree of kinship with the deceased. Such a solution means that persons completely alien to the deceased, but only formally related to them, may be appointed to inherit, which is not approval-worthy. For this reason, the proposed change of the Civil Code, providing for the inheritance of the descendants of grandparents up to the fourth degree of kinship with the deceased, should be considered justified.